A Case of RhabdomyoSarcoma Following a Metal Surgical Implant. (1999) - Gatti, Giovanna M.; Ivaldi, Giovanni B.; Lartigau, Eric; Marsiglia, Hugo; Orecchia, Roberto
Abstract : Patient. We report a 51-year-old male presenting with Grade III rhabdomyosarcoma. Discussion. A case of rhabdomyosarcoma which developed in proximity to a metal surgical implant is described. Few cases have been reported in the world in humans.The therapeutic approach to the disease is presented, together with a brief review of literature.